2011
DOI: 10.1007/s11803-011-0059-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of near-fault earthquakes with forward directivity on telecommunication towers

Abstract: In this paper, the effect of pulse-type motions caused by forward directivity that can release huge amounts of energy in a short time period is studied on a telecommunication tower. Since telecommunication towers have longer periods, they are not as affected by seismic forces. Nevertheless, near source earthquakes characterized by high velocity and velocity pulses can change the behavior of these structures. For this reason, a telecommunication tower located near active faults was selected in this study. Consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The main characteristics of these impulse motions are the period and maximum velocity pulse amplitudes. The velocity pulse has specific characteristics of near-fault earthquakes that cannot be observed in far-field earthquakes [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main characteristics of these impulse motions are the period and maximum velocity pulse amplitudes. The velocity pulse has specific characteristics of near-fault earthquakes that cannot be observed in far-field earthquakes [24].…”
Section: Introductionmentioning
confidence: 99%
“…The velocity waveforms were chosen to identify the pulse signals because it is easier to detect the pulse from the velocity [27,30]. Owing to these unique characteristics of near-fault ground motions, the seismic responses of civil engineering structures, such as buildings, tunnels, bridges, nuclear stations, dams, towers, viaducts, wind turbines, and tanks, under near-fault ground motions have received a great deal of attention over the last decades [5,7,11,24,28,30,[32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…Since the amplitude of the fling-step is highly sensitive to the choice of baseline, and baseline correction has a negligible effect on elastic response spectra, records are typically filtered and added to an engineering database [6]. Previous studies showed that structural response due to near field earthquakes is more severe than that of far-field records, and significantly depends on the pulse period to structure period [7][8][9][10]. There are only a few studies on the effect of near-field earthquakes with the fling-step effect.…”
Section: Introductionmentioning
confidence: 99%